2007
DOI: 10.1159/000101847
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal Lobar Degeneration with Ubiquitin-Positive Inclusions: A Molecular Genetic Update

Abstract: Frontotemporal lobar degeneration (FTLD) is a clinically, pathologically and genetically highly complex disorder. In the last few years enormous progress has been made in dissecting the genetic etiology of FTLD. Mutations have been identified in the progranulin gene (PGRN), the charged multivesicular body protein 2B gene (CHMP2B) and the valosin-containing protein gene (VCP). Mutations in these genes all lead to FTLD pathology characterized by ubiquitin-immunoreactive neuronal cytoplasmic and intranuclear lent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…The intronic variant IVS2 ?7 G [ A has been identified in one patient, this variant was already listed in the first reported GRN screens ( Van der Zee et al 2007;Sleegers et al 2008), and it was observed to have a low frequency both in patients and controls. We did not find this mutation in 210 controls.…”
Section: Resultsmentioning
confidence: 71%
“…The intronic variant IVS2 ?7 G [ A has been identified in one patient, this variant was already listed in the first reported GRN screens ( Van der Zee et al 2007;Sleegers et al 2008), and it was observed to have a low frequency both in patients and controls. We did not find this mutation in 210 controls.…”
Section: Resultsmentioning
confidence: 71%
“…The identification of a common genetic cause and subsequent pathological manifestation in both FTLD and ALS provided concrete evidence that these two diseases exist as a part of a common disease spectrum. C9orf72 and GRN mutations likely account for over half of all familial occurrences of FTLD-TDP; however, mutations in the genes encoding tank-binding kinase 1 ( TBK1) and the valosin containing protein ( VCP) have also been discovered as less common genetic causes in patients with FTLD-TDP [20, 23, 46, 54, 77, 84]. In rare cases of FTLD-U, the ubiquitinated protein is a TDP-43 protein family member known as fused in sarcoma (FUS) [50, 67], but there is no known genetic cause for this pathological subtype.…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of frontotemporal lobar degeneration (FTLD) with transactive response (TAR) DNA-binding protein of 43kDa (TDP-43) proteinopathy (FTLD-TDP) cases are familial [1][2][3][4][5][6][7][8]. Various genetic defects have been identified in these cases, the majority being caused by mutation of the progranulin (GRN) gene [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Various genetic defects have been identified in these cases, the majority being caused by mutation of the progranulin (GRN) gene [2][3][4][5][6][7][8][9]. Familial FTLD-TDP can also be commonly caused by chromosome 9 open reading frame 72 (C9ORF72) gene [10,11] and more rarely by valosincontaining protein (VCP) gene mutation [12].…”
Section: Introductionmentioning
confidence: 99%